ROLE OF THE FAMILY IN FORMATION OF CHILDREN CHARACTERS BASED MORAL KNOWING, MORAL FEELING, AND MORAL ACTION - Doli Witro; Berlian Arista Putri; Luqyana Azmiya Putri; Vegia Oviensy (Universitas Islam Negeri Palopo, 2020)
The family is the closest thing to starting the process of character development in children. Parents are the primary mentors in the family environment. Parents have a duty as an example that teaches noble values in children. The family is an informal educational institution, while formal education institutions are schools. There are essential aspects in fostering the character of children, namely the understanding of ethics (moral knowing), the embodiment of characteristics (moral action), and the instinct of morality (moral feeling). As a parent, not only must pay attention to the three aspects above but also pay attention to their duties as guiding children to have ethical behavior. This study aims to determine the relationship of family roles in the formation of children’s character based on moral understanding, feelings about morals, and moral conduct. This research method uses qualitative research with the type of library research. Qualitative research with this type of literature study can produce data like information obtained through the interview process and is strengthened by describing the findings of research on the problem under study. The type of data needed comes from books, journals, scientific articles, etc. that are obtained by reading as much as possible. Data analysis methods used include data reduction, data display, and data verification (concluding). This study aims to see how moral knowing, moral feeling, and moral action are applied in the family. The results of this study are expected to provide in-depth information about the role of the family in shaping children’s character based on moral knowing, moral feeling, and moral action.